Study on the T-Cell Immune Response in Individuals With HIV and Toxoplasmosis Using ELISPOT - Iskra Georgieva Rainova; Rumen Nenkov Harizanov; Yana Dimitrova Todorova; Mihaela Vanyova Videnova; Eleonora Marinova Kaneva; Raina Borisova Enikova; Nina Dimitrova Tsvetkova (Interdisciplinary Perspectives on Infectious Diseases)
Conclusion: It is important to monitor patients with HIV, toxoplasmosis, and immunodeficiency. This can help prevent complications such as TE. A modified ELISPOT protocol may be required to determine the specific cell-mediated response in immunocompromised patients.